Foundations of Global Health &Amp; Human Rights 2020
DOI: 10.1093/oso/9780197528297.003.0021
|View full text |Cite
|
Sign up to set email alerts
|

Global Health and Human Rights in the Age of Populism

Abstract: This chapter examines the threat of populism to global health and human rights. Out of the ashes of World War II, institutions of global health and human rights have brought the world together in unprecedented cooperation, giving rise to the successes and opportunities detailed throughout this text. However, the current populist age threatens these successes and raises obstacles to future progress. In violent contrast with the shared goals of a globalizing world, populism seeks to retrench nations inward, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…Poprzez jej praktyczną realizację organizacje wymieniają się wartościami z otoczeniem, co w konsekwencji przekłada się na kreowanie trwałych relacji. W tym celu konieczne jest rozpoznanie istoty dysfunkcji posiadanych przez reprezentantów poszczególnych grup interesariuszy (Fetzki, Fetzka, 2020) oraz generowanych przez nie barier i trudności (Gostin, Meier, 2020;Jarman, Monaghan, Harkin, 2017). Ograniczenia te określane są nie tylko przez własne ciało i psychikę, ale również przez system społeczny.…”
Section: Obszary Wsparcia Osób Z Niepełnosprawnością Przez Organizacjeunclassified
See 1 more Smart Citation
“…Poprzez jej praktyczną realizację organizacje wymieniają się wartościami z otoczeniem, co w konsekwencji przekłada się na kreowanie trwałych relacji. W tym celu konieczne jest rozpoznanie istoty dysfunkcji posiadanych przez reprezentantów poszczególnych grup interesariuszy (Fetzki, Fetzka, 2020) oraz generowanych przez nie barier i trudności (Gostin, Meier, 2020;Jarman, Monaghan, Harkin, 2017). Ograniczenia te określane są nie tylko przez własne ciało i psychikę, ale również przez system społeczny.…”
Section: Obszary Wsparcia Osób Z Niepełnosprawnością Przez Organizacjeunclassified
“…8 Królikowski, 2018;Toquero, 2020). W tym celu konieczne jest rozpoznanie istoty dysfunkcji posiadanych przez reprezentantów poszczególnych grup interesariuszy (Fetzki, Fetzka, 2020) oraz generowanych przez nie barier i trudności (Gostin, Meier, 2020;Jarman, Monaghan, Harkin, 2017). Ograniczenia te określane są nie tylko przez własne ciało i psychikę, ale również Działania makro głównie dotyczą ogólnych inicjatyw społecznych, które wykraczają poza podstawowy obszar działalności przedsiębiorstwa oraz stanowią przejaw dobrej woli wobec otoczenia.…”
Section: Obszary Wsparcia Osób Z Niepełnosprawnością Przez Organizacjeunclassified
“…13 These nationalist policies have transgressed international law, with cascading effects on international trade, health determinants, and human rights. 14 Rather than working together to fight a common threat, nationalist strategies pit nations against nations, subvert global action to curb the pandemic, and grind the world to a standstill.…”
Section: Obstacles To Global Solidaritymentioning
confidence: 99%
“…WE are when a person discovers joy in work in spite of strenuous employment requests and stressors ( Ungar & Theron, 2020 ; Gostin, Constantin & Meier, 2020 ). Nishi et al (2016) demonstrated that WE is an indicator of wellbeing, higher life fulfillment, and predominant occupation execution, with low depressive disorders.…”
Section: Introductionmentioning
confidence: 99%
“… Nishi et al (2016) demonstrated that WE is an indicator of wellbeing, higher life fulfillment, and predominant occupation execution, with low depressive disorders. Henceforth, WE includes performing task without stressing and interchanging ideas and plan for better performance and outcomes ( Gostin, Constantin & Meier, 2020 ; Atroszko & Atroszko, 2020 ). Moreover, WE promotes the state of being comfortable, healthy, or happy and a stress free life ( Sharma, 2017 ).…”
Section: Introductionmentioning
confidence: 99%